Multi-layer container

The multilayer container structure with a polyester, polyamide, and polyglycolic acid layers, enhanced by an oxidation promoter, addresses thermal instability and oxygen barrier issues, providing improved performance for heated beverages and foods.

JP7622396B2Active Publication Date: 2025-01-28MITSUBISHI GAS CHEM CO INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020185987
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-06
Publication Date
2025-01-28
Estimated Expiration
2040-11-06

AI Technical Summary

Technical Problem

Polyester resin containers exhibit insufficient thermal stability and oxygen barrier properties, particularly when used for beverages and foods that are heated, and they suffer from delamination due to differences in resin layers with varying properties.

Method used

A multilayer container structure comprising a polyester layer, a polyamide resin layer, and a polyglycolic acid layer, with specific mass ratios and molecular compositions, including an oxidation promoter, to enhance oxygen barrier and thermal stability while preventing delamination.

Benefits of technology

The multilayer container achieves improved oxygen barrier, thermal stability, and delamination resistance, making it suitable for beverages and foods that are heated or subject to mechanical stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622396000002
    Figure 0007622396000002
  • Figure 0007622396000001
    Figure 0007622396000001
Patent Text Reader

Abstract

To provide a multi-layered container excellent in oxygen barrier properties and thermal stability and also in delamination resistance, and a method of manufacturing the same.SOLUTION: A multi-layered container 5 comprises a polyester layer containing an aromatic polyester resin (A) and a resin mixture layer containing polyamide resin (B), polyglycolic acid (C) and pro-oxidant (D). The resin mixture layer contains the polyamide resin (B) and the polyglycolic acid (C) at a mass ratio [(B) / (C)] of 25 / 75-95 / 5. The polyamide resin (B) has a constitutional unit derived from diamine containing 70 mol% or more of a constitutional unit derived from xylylene-diamine, and a constitutional unit derived from dicarboxylic acid containing 70 mol% or more of a constitutional unit derived from α,ω-straight-chain aliphatic dicarboxylic acid having 4-20 carbons.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multi-layer container. [Background technology]

[0002] Polyester resins, typified by polyethylene terephthalate (PET), are characterized by excellent transparency, mechanical properties, melt stability, recyclability, etc., and are therefore currently widely used in various packaging materials such as films, sheets, and hollow containers. On the other hand, particularly in bottle applications, hollow containers made only of polyester resin do not have sufficient gas barrier properties against carbon dioxide, oxygen, etc., so attempts have been made to improve the gas barrier properties by multi-layering with resins that have excellent gas barrier properties. For example, Patent Document 1 discloses a multilayer structure having a barrier layer made of a polyamide containing an aromatic ring in the skeleton, which is obtained from a diamine component mainly composed of an aromatic diamine and a dicarboxylic acid, and a polyglycolic acid or a polyethylene oxalate, in order to improve the barrier property under high humidity conditions, heat resistance, and moldability. Furthermore, Patent Document 2 discloses a plastic container having a multi-layer structure with one or more gas barrier layers as a container having long-lasting gas barrier properties, in which a thin film mainly composed of an inorganic oxide is formed on the entire inside surface of the container. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2007-211159 A [Patent Document 2] JP 2005-271959 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, polyester resin containers have been used not only for soft drinks but also for various drinks and foods. For example, they are used for drinks that are always heated and used, and for drinks and foods that are filled at high temperatures, and one of the important properties of polyester resin containers is thermal stability, which means that there is little change in dimensions at high temperatures. The containers in the above patent documents still do not have sufficient thermal stability, and although the gas barrier properties are improved compared to conventional containers, there has been a demand for containers with even better gas barrier properties, especially oxygen barrier properties, as the contents become more diverse. In addition, there is also a problem that the resin layers peel off (delamination) when resins with different properties and molecular structures are multi-layered. Therefore, an object of the present invention is to provide a multilayer container having excellent oxygen barrier properties, thermal stability, and delamination resistance, and a method for producing the same. [Means for solving the problem]

[0005] As a result of intensive research in view of the above problems, the present inventors have found that the above problems can be solved by a multi-layer container having a polyester layer and a mixed resin layer containing a specific polyamide resin and polyglycolic acid in a specific ratio and further containing an oxidation promoter, and have completed the present invention. The present invention provides the following [1] to

[10] .

[0006] [1] A multilayer container comprising a polyester layer containing an aromatic polyester resin (A) and a mixed resin layer containing a polyamide resin (B), a polyglycolic acid (C) and an oxidation promoter (D), wherein the mass ratio [(B) / (C)] of the polyamide resin (B) to the polyglycolic acid (C) in the mixed resin layer is 25 / 75 to 95 / 5, and the polyamide resin (B) has structural units derived from a diamine containing 70 mol % or more of structural units derived from a xylylenediamine and structural units derived from a dicarboxylic acid containing 70 mol % or more of structural units derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. [2] The multilayer container according to [1], which has a 2 to 5 layer structure. [3] The multilayer container according to [1] or [2], which has a two-layer structure in which a polyester layer / mixed resin layer is laminated in this order from the outside of the container, a three-layer structure in which a polyester layer / mixed resin layer / polyester layer is laminated in this order, or a five-layer structure in which a polyester layer / mixed resin layer / polyester layer / mixed resin layer / polyester layer is laminated in this order. [4] The multilayer container according to any one of [1] to [3], wherein the pro-oxidant (D) is an aliphatic carboxylate of cobalt. [5] The multilayer container according to any one of [1] to [4], wherein the thickness of all layers of the multilayer container is 50 to 500 μm. [6] The multilayer container according to any one of [1] to [5], having a capacity of 200 to 600 mL. [7] The multilayer container according to any one of [1] to [6], wherein the aromatic polyester resin (A) has structural units derived from a dicarboxylic acid containing 90 mol % or more of structural units derived from terephthalic acid, and structural units derived from a diol containing 90 mol % or more of structural units derived from ethylene glycol. [8] The multilayer container according to any one of [1] to [7], wherein the polyamide resin (B) has structural units derived from a diamine containing 80 mol % or more of structural units derived from xylylenediamine, and structural units derived from a dicarboxylic acid containing 80 mol % or more of structural units derived from adipic acid. [9] The multilayer container according to any one of [1] to [8], wherein the mass ratio [(B) / (C)] of the polyamide resin (B) to the polyglycolic acid (C) in the mixed resin layer is 55 / 45 to 75 / 25.

[10] The multilayer container according to any one of [1] to [9], wherein the polyester layer contains an aromatic polyester resin (A) and a polyglycolic acid (C). Effect of the Invention

[0007] According to the present invention, it is possible to provide a multilayer container having excellent oxygen barrier properties, thermal stability, and delamination resistance, and a method for producing the same. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a conceptual schematic diagram showing each step of cold parison molding. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The multilayer container of the present invention has a polyester layer containing an aromatic polyester resin (A) and a mixed resin layer containing a polyamide resin (B), polyglycolic acid (C) and an oxidation promoter (D), in which the mass ratio [(B) / (C)] of the polyamide resin (B) to the polyglycolic acid (C) in the mixed resin layer is 25 / 75 to 95 / 5, and the polyamide resin (B) has structural units derived from a diamine containing 70 mol % or more of structural units derived from a xylylenediamine and structural units derived from a dicarboxylic acid containing 70 mol % or more of structural units derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms. The present invention will be described in detail below.

[0010] [Polyester layer] The polyester layer constituting the multilayer container of the present invention contains an aromatic polyester resin (A).

[0011] <Aromatic polyester resin (A)> The aromatic polyester resin (A) used in the present invention may be a copolymer of a dicarboxylic acid and a diol, a polymer of a lactone or a hydroxycarboxylic acid, or a copolymer of a mixture of these monomers, with a copolymer of a dicarboxylic acid and a diol being preferred. A preferred aromatic polyester resin (A) has a constitutional unit derived from a dicarboxylic acid (hereinafter also referred to as a "dicarboxylic acid unit") and a constitutional unit derived from a diol (hereinafter also referred to as a "diol unit").

[0012] The dicarboxylic acid unit preferably contains 90 mol% or more of the constitutional unit derived from terephthalic acid, more preferably 95 mol% or more, and even more preferably 99 mol% or more. There is no upper limit, and it is 100 mol% or less. If the constitutional unit derived from terephthalic acid in the dicarboxylic acid unit is 90 mol% or more, the polyester resin is unlikely to become amorphous, and therefore, when the polyester resin is used to produce a container, the polyester resin is unlikely to shrink due to heat and has good heat resistance. The diol unit preferably contains 90 mol % or more of constitutional units derived from ethylene glycol, more preferably 95 mol % or more, and even more preferably 99 mol % or more. There is no upper limit, but it is 100 mol % or less. In other words, as a combination of dicarboxylic acid units and diol units of the aromatic polyester resin (A), it is preferable that the aromatic polyester resin (A) has structural units derived from dicarboxylic acid containing 90 mol % or more of structural units derived from terephthalic acid and structural units derived from diol containing 90 mol % or more of structural units derived from ethylene glycol, and it is more preferable that the main component is polyethylene terephthalate.

[0013] The aromatic polyester resin (A) may contain structural units derived from a bifunctional compound, such as a dicarboxylic acid other than terephthalic acid, or a diol other than ethylene glycol. Examples of the dicarboxylic acid other than terephthalic acid include sulfophthalic acid, metal salts of sulfophthalic acid, and aromatic dicarboxylic acids other than terephthalic acid. The aromatic dicarboxylic acid other than terephthalic acid is preferably isophthalic acid, orthophthalic acid, naphthalenedicarboxylic acid, or 4,4'-biphenyldicarboxylic acid. As the diol other than ethylene glycol, neopentyl glycol and cyclohexanedimethanol are preferred.

[0014] Furthermore, the aromatic polyester resin (A) may contain structural units derived from a monofunctional compound such as a monocarboxylic acid or a monoalcohol, and may contain structural units derived from a polyfunctional compound having at least three ester-forming groups selected from a carboxy group and a hydroxy group.

[0015] The aromatic polyester resin (A) can be produced by a known direct esterification method or transesterification method. The polycondensation catalyst used in the production of the aromatic polyester resin (A) can be an antimony compound, a germanium compound, an aluminum compound, or the like. The aromatic polyester resin (A) may also contain recycled polyester, or may be a mixture of two or more resins.

[0016] The intrinsic viscosity of the aromatic polyester resin (A) is not particularly limited, but is preferably 0.5 to 2.0 dl / g, more preferably 0.6 to 1.5 dl / g. If the intrinsic viscosity is 0.5 dl / g or more, the molecular weight of the polyester resin is sufficiently high, so that the container can exhibit the mechanical properties required as a structure. The intrinsic viscosity was measured by dissolving the polyester resin to be measured in a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (=6 / 4 mass ratio) to prepare 0.2, 0.4, and 0.6 g / dL solutions, and measuring the intrinsic viscosity at 25°C using an automatic viscosity measuring device (Viscotek, manufactured by Malvern Instruments).

[0017] <Resins other than aromatic polyester resin (A)> In the container of the present invention, the polyester layer may contain a resin other than the aromatic polyester resin (A) as long as the effect of the present invention is not impaired. From the viewpoint of delamination resistance, the resin other than the aromatic polyester resin (A) is preferably an aliphatic polyester resin, and more preferably polyglycolic acid. As the polyglycolic acid, the polyglycolic acid defined as polyglycolic acid (C) described later is more preferable. That is, when a resin other than the aromatic polyester resin (A) is contained, it is more preferable that the polyester layer contains the aromatic polyester resin (A) and the polyglycolic acid (C). When the polyester layer contains the polyglycolic acid (C), the content of the polyglycolic acid (C) is preferably 1 to 20 mass%, more preferably 2 to 15 mass%, and further preferably 5 to 10 mass%. The content of the aromatic polyester resin (A) in the polyester layer is preferably 90% by mass or more, more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 99% by mass or more. There is no upper limit, but it is 100% by mass or less.

[0018] <Other ingredients> An example of other components contained in the polyester layers constituting the multi-layer container of the present invention is a recycling aid.

[0019] The recycling aid is a compound that has the effect of suppressing yellowing in the recycling step when obtaining recycled polyester, and as the recycling aid, an aldehyde scavenger is preferable. The recycling aid is preferably a compound that has the ability to suppress yellowing of the polyester resin and contains an amino group, and more specifically, it is more preferably at least one compound selected from the group consisting of anthranilamide, anthranilic acid, and nylon 6I / 6T.

[0020] In addition to the above components, the polyester layer may contain additives such as a colorant, a heat stabilizer, a light stabilizer, a moisture-proofing agent, a waterproofing agent, a lubricant, and a spreading agent.

[0021] As the colorant, white, green, brown, blue, and black dyes and white, green, brown, blue, and black pigments are preferred. By including a colorant, light-shielding properties are imparted, the contents can be protected, and the design is excellent, which is preferable. As the colorant, a master batch in which a pigment or the like is dispersed in a resin is preferably used.

[0022] [Mixed resin layer] The mixed resin layer constituting the multilayer container of the present invention contains a polyamide resin (B), polyglycolic acid (C) and an oxidation promoter (D). The mass ratio [(B) / (C)] of the polyamide resin (B) to the polyglycolic acid (C) in the mixed resin layer is 25 / 75 to 95 / 5, preferably 30 / 70 to 90 / 10, more preferably 40 / 60 to 80 / 20, even more preferably 45 / 55 to 75 / 25, and even more preferably 55 / 45 to 75 / 25. By setting the ratio of the polyamide resin to the polyglycolic acid in the above range, excellent heat resistance is achieved while maintaining high oxygen absorption.

[0023] <Polyamide resin (B)> The polyamide resin (B) has structural units derived from a diamine containing 70 mol % or more of structural units derived from xylylenediamine (hereinafter also referred to as diamine units), and structural units derived from a dicarboxylic acid containing 70 mol % or more of structural units derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms (hereinafter also referred to as dicarboxylic acid units).

[0024] As the diamine, which is a compound constituting the diamine-derived constitutional unit (hereinafter also referred to as the diamine unit) of the polyamide resin (B), xylylenediamine is preferred. The polyamide resin (B) contains 70 mol% or more of xylylenediamine-derived structural units in the diamine-derived structural units, preferably 80 mol% or more, more preferably 90 mol% or more, and even more preferably 95 mol% or more. There is no upper limit, and it is 100 mol% or less. By making 70 mol% or more of the diamine units be xylylenediamine-derived structural units, it is possible to impart high gas barrier properties to the multilayer container of the present invention. The xylylenediamine may be any of ortho-, meta-, and para-xylylenediamine, but meta-xylylenediamine is preferred from the viewpoint of availability.

[0025] As the compound constituting the diamine unit of the polyamide resin (B), diamines other than xylylenediamine include diamines having an aromatic ring structure, aliphatic diamines, and diamines having an alicyclic structure. Of these, aliphatic diamines are preferred from the viewpoints of easy availability and enhanced colorlessness and adhesion.

[0026] Examples of the aliphatic diamine include tetramethylenediamine, hexamethylenediamine, nonamethylenediamine, 2-methyl-1,5-pentanediamine, undecamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, 2,4,4-trimethylhexamethylenediamine, and 5-methylnonamethylenediamine. Examples of diamines having an alicyclic structure include 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1-amino-3-aminomethylcyclohexane, bis(4-aminocyclohexyl)methane, bis(3-methyl-4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminopropyl)piperazine, and aminoethylpiperazine. Incidentally, polyamines having a valence of three or more, such as bis(hexamethylene)triamine, and monoamines, such as butylamine, hexylamine, and octylamine, may also be used within the scope of the present invention.

[0027] The polyamide resin (B) preferably contains 70 mol % or more of structural units derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms in the dicarboxylic acid units, more preferably 80 mol % or more, even more preferably 90 mol % or more, and even more preferably 95 mol % or more. There is no upper limit, and it is 100 mol % or less. By making 70 mol % or more of the dicarboxylic acid units structural units derived from an α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms, the colorlessness and delamination resistance of the obtained multilayer container can be efficiently improved.

[0028] Examples of α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms include succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, 1,10-decanedicarboxylic acid, 1,11-undecanedicarboxylic acid, and 1,12-dodecanedicarboxylic acid, with adipic acid and sebacic acid being preferred, and adipic acid being more preferred. These α,ω-linear aliphatic dicarboxylic acids may be used alone or in combination of two or more.

[0029] Examples of compounds that can constitute the dicarboxylic acid unit of the polyamide resin (B) include, in addition to α,ω-straight-chain aliphatic dicarboxylic acids having 4 to 20 carbon atoms, dicarboxylic acids having an alicyclic structure such as 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, decalindicarboxylic acid, norbornanedicarboxylic acid, tricyclodecanedicarboxylic acid, pentacyclododecanedicarboxylic acid, isophoronedicarboxylic acid, and 3,9-bis(2-carboxyethyl)-2,4,8,10-tetraoxaspiro[5.5]undecane; and dicarboxylic acids having an aromatic ring structure such as terephthalic acid, isophthalic acid, phthalic acid, orthophthalic acid, 2-methylterephthalic acid, naphthalenedicarboxylic acid, biphenyldicarboxylic acid, and tetralindicarboxylic acid. In addition, polyvalent carboxylic acids having three or more valences, such as trimellitic acid, trimesic acid, pyromellitic acid, and tricarballylic acid, may be used as long as the effects of the present invention are not impaired, and monocarboxylic acids may also be used.

[0030] In addition to the above-mentioned diamine units and dicarboxylic acid units, the units constituting the polyamide resin (B) may contain structural units derived from aminocarboxylic acids, etc., within the scope that does not impair the effects of the present invention. Specific examples of such structural units include structural units derived from aliphatic aminocarboxylic acids and structural units derived from aromatic aminocarboxylic acids.

[0031] The compounds constituting the dicarboxylic acid, polycarboxylic acid and monocarboxylic acid used in the dicarboxylic acid unit include anhydrides and short-chain alkyl esters.Specific examples of the short-chain alkyl esters include those having 1 to 3 carbon atoms, that is, methyl esters, ethyl esters, propyl esters and isopropyl esters, and among these, methyl esters are preferred.In addition, the compounds constituting the structural unit derived from aminocarboxylic acid include lactams, which are anhydrides.

[0032] The combination of diamine units and dicarboxylic acid units in polyamide resin (B) is such that polyamide resin (B) has structural units derived from diamine containing 70 mol % or more of structural units derived from xylylenediamine and structural units derived from dicarboxylic acid containing 70 mol % or more of structural units derived from α,ω-linear aliphatic dicarboxylic acid having 4 to 20 carbon atoms, but it is preferable that polyamide resin (B) has structural units derived from diamine containing 80 mol % or more of structural units derived from xylylenediamine and structural units derived from dicarboxylic acid containing 80 mol % or more of structural units derived from adipic acid.

[0033] Specific examples of the polyamide resin (B) in the present invention include polyamide MXD6 (polymetaxylylene adipamide), polyamide MXD10 (polymetaxylylene sebacamide), polyamide MXD6I (isophthalic acid copolymerized polymetaxylylene adipamide), etc., and from the viewpoints of availability, gas barrier properties, and colorlessness, polyamide MXD6 or polyamide MXD10 is preferred, and polyamide MXD6 is more preferred. These polyamide resins may be used alone or in combination of two or more kinds.

[0034] (Production method of polyamide resin (B)) The polyamide resin (B) is preferably produced by a melt polycondensation method. The melt polycondensation method is preferably a method of directly adding diamine to molten dicarboxylic acid and polycondensing it. In this case, in order to keep the reaction system in a homogeneous liquid state, it is preferable to continuously add diamine to dicarboxylic acid and to proceed with polycondensation while increasing the temperature of the reaction system so that the reaction temperature does not fall below the melting points of the oligoamide and polyamide produced.

[0035] It is preferable to add a phosphorus atom-containing compound to the polycondensation reaction system of the polyamide resin (B) in order to obtain the effect of accelerating the amidation reaction and the effect of preventing coloration during the polycondensation reaction. As the phosphorus atom-containing compound, metal hypophosphites such as sodium hypophosphite, potassium hypophosphite, lithium hypophosphite, and calcium hypophosphite are preferred, and sodium hypophosphite is more preferred, because they have a high effect of promoting the amidation reaction and also have an excellent effect of preventing discoloration.

[0036] The amount of the phosphorus atom-containing compound added to the polyamide resin (B) polycondensation reaction system is preferably 1 to 500 ppm, more preferably 5 to 450 ppm, and even more preferably 10 to 400 ppm, calculated as the phosphorus atom concentration in the polyamide resin (B). By setting the amount of the phosphorus atom-containing compound to be within the above range, coloration of the polyamide during the polycondensation reaction can be prevented and gelation of the polyamide can be suppressed, so that the appearance of the resulting container can be maintained in a good condition. In addition, an alkali metal compound and / or an alkaline earth metal compound may be added in combination with the phosphorus atom-containing compound to the polycondensation reaction system of the polyamide resin (B).

[0037] The polyamide resin (B) obtained by the melt polycondensation method is preferably pelletized and then dried before use, and more preferably subjected to solid-phase polymerization in order to further increase the degree of polymerization. The solid-state polymerization is preferably carried out by heating the pellets under reduced pressure.

[0038] (Properties of polyamide resin (B)) The relative viscosity of the polyamide resin (B) is preferably from 1.5 to 4.2, more preferably from 1.6 to 4.0, even more preferably from 1.7 to 3.8, and still more preferably from 1.9 to 3.0. By setting the relative viscosity of the polyamide resin (B) within the above range, the molding processability is stable, and a container with good appearance can be obtained. In the present invention, the relative viscosity of the polyamide resin (B) is measured by the following method. Specifically, 0.2 g of the polyamide resin is precisely weighed and dissolved in 20 ml of 96% by mass sulfuric acid at 20 to 30°C with stirring. After complete dissolution, 5 ml of the solution is quickly taken in a Cannon-Fenske viscometer, and the solution is left in a thermostatic bath at 25°C for 10 minutes, after which the drop time (t) of the solution is measured. The drop time (t0) of 96% by mass sulfuric acid is also measured in the same manner. The relative viscosity of the polyamide resin is calculated from the measured values ​​of t and t0 according to the following formula. Relative viscosity=t / t0

[0039] The content of the polyamide resin (B) in the mixed resin layer is preferably 25% by mass or more, more preferably 55% by mass or more, even more preferably 70% by mass or more, and even more preferably 75% by mass or more, and is preferably 95% by mass or less, and more preferably 90% by mass or less. When the content of polyamide resin (B) is 25% by mass or more, oxygen permeability can be sufficiently suppressed and thermal stability can be improved, and when the content is 95% by mass or less, the delamination resistance of the resulting container is improved. In particular, from the viewpoint of further improving the delamination resistance, the content of the polyamide resin (B) in the mixed resin layer is preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 45% by mass or more, and even more preferably 55% by mass or more, and is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less.

[0040] <Polyglycolic acid (C)> Polyglycolic acid (C) is a polymer of glycolic acid and contains the structural unit [-O-CH2-CO-] derived from glycolic acid. The proportion of the structural units is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, with the upper limit being 100% by mass. Examples of the structural unit other than the above-mentioned structural unit include [-O-(CH2) n -O-CO-(CH2) m -CO-] (where n = 1 to 10, m = 0 to 10), [-O-CH(CH2) j H-CO-] (where j = 1 to 10), [-O-(CR 1 R 2 ) k -CO-] (where R 1 , R 2 are each independently a hydrogen atom or an alkyl group having 1 to 10 carbon atoms (k=2 to 10), [-O-CH2-CH2-CH2-O-CO-], [-O-CH2-O-CH2-CH2-], etc., and the melting point, molecular weight, viscosity, etc. of the polyglycolic acid (C) can be adjusted by these structural units.

[0041] The polyglycolic acid (C) can be produced by known methods, such as condensation polymerization of glycolic acid or an ester of glycolic acid, and ring-opening polymerization of glycolide.

[0042] The polyglycolic acid (C) has a glass transition temperature of preferably 30 to 45° C., more preferably 35 to 40° C., a melting point of preferably 215 to 230° C., more preferably 220 to 225° C., and a crystallization temperature of preferably 60 to 100° C., more preferably 80 to 95° C., and even more preferably 85 to 95° C. These temperatures are measured in accordance with JIS K7121.

[0043] The content of polyglycolic acid (C) in the mixed resin is preferably 5% by mass or more, more preferably 10% by mass or more, and is preferably 75% by mass or less, more preferably 45% by mass or less, even more preferably 30% by mass or less, and even more preferably 25% by mass or less. When the content of polyglycolic acid (C) is 5% by mass or more, the delamination resistance of the resulting container can be improved, and when it is 75% by mass or less, the oxygen barrier property and thermal stability can also be improved. In particular, from the viewpoint of further improving the delamination resistance, the content of the polyglycolic acid (C) in the mixed resin is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, and is preferably 70% by mass or less, more preferably 60% by mass or less, even more preferably 55% by mass or less, and even more preferably 45% by mass or less.

[0044] <Prooxidant (D)> In the present invention, the mixed resin layer contains an oxidation promoter (D) for the purpose of inducing an oxidation reaction of the resin to enhance the oxygen absorbing function and further enhance the oxygen barrier property. The oxidation promoter (D) is preferably a compound containing a transition metal, and more preferably at least one selected from the group consisting of a simple transition metal, an oxide, an inorganic acid salt, an organic acid salt, and a complex. Examples of inorganic acid salts include halides such as chlorides and bromides, carbonates, sulfates, nitrates, phosphates, and silicates. Examples of the organic acid salt include carboxylates, sulfonates, and phosphonates. The complexes include complexes with β-diketones or β-keto acid esters. The transition metal contained in the transition metal-containing compound is preferably at least one selected from the group consisting of transition metals of Group VIII of the periodic table, manganese, copper, and zinc, and from the viewpoint of exhibiting oxygen absorption ability, more preferably at least one selected from the group consisting of cobalt, iron, manganese, and nickel, and even more preferably cobalt. The carboxylate is preferably an aliphatic carboxylate. Examples of the aliphatic carboxylate include octanoates, neodecanoates, naphthenates, stearates, acetates, etc., and among these, stearates are preferred. From the viewpoint of exhibiting good oxygen absorption capacity, it is preferable to use at least one selected from the group consisting of aliphatic carboxylates of transition metals and acetylacetonate complexes of transition metals, it is more preferable to use at least one selected from the group consisting of octanoates, neodecanoates, naphthenates, stearates, acetates and acetylacetonate complexes, it is even more preferable to use an aliphatic carboxylate of cobalt, and even more preferable to use one or more selected from cobalt octanoate, cobalt naphthenate, cobalt acetate and cobalt stearate.

[0045] The pro-oxidant (D) may be used alone or in combination of two or more kinds. The content of the oxidation promoter (D) in the mixed resin layer is preferably 100 to 10,000 ppm, more preferably 200 to 8,000 ppm, further preferably 500 to 6,000 ppm, and even further preferably 800 to 5,000 ppm, from the viewpoints of improving the gas barrier property and oxygen absorbing property. When a compound containing a transition metal is used as the oxidation promoter (D), the content of the oxidation promoter (D) in the mixed resin layer is preferably 10 to 1,000 ppm, more preferably 20 to 800 ppm, even more preferably 50 to 600 ppm, and even more preferably 80 to 500 ppm, calculated as the transition metal. Note that "in terms of the transition metal" refers to the content of the transition metal itself in the compound containing the transition metal. Also, ppm is based on mass.

[0046] <Other ingredients> An example of another component contained in the mixed resin layer constituting the multilayer container of the present invention is a recycling aid.

[0047] The recycling aid is a compound that has the effect of suppressing yellowing in the recycling step when obtaining recycled polyester, and as the recycling aid, an aldehyde scavenger is preferable. The recycling aid is preferably a compound that has the ability to suppress yellowing of the polyester resin and contains an amino group, and more specifically, it is more preferably at least one compound selected from the group consisting of anthranilamide, anthranilic acid, and nylon 6I / 6T.

[0048] The mixed resin layer may contain, in addition to the above components, additives such as a heat stabilizer, a light stabilizer, a moisture-proofing agent, a waterproofing agent, a lubricant, and a spreading agent.

[0049] [Multilayer container] The multilayer container of the present invention is preferably a hollow container, and when the multilayer container is a hollow container, at least the body portion has a multilayer laminate structure. The multilayer container of the present invention preferably has a 2- to 5-layer structure, more preferably a 2-, 3- or 5-layer structure, even more preferably a 3- or 5-layer structure, and even more preferably a 3-layer structure. Specifically, from the outside of the container, it is preferable for the structure to be any one of a two-layer structure in which a polyester layer / mixed resin layer is laminated in this order, a three-layer structure in which a polyester layer / mixed resin layer / polyester layer is laminated in this order, or a five-layer structure in which a polyester layer / mixed resin layer / polyester layer / mixed resin layer / polyester layer is laminated in this order.

[0050] The multilayer container of the present invention may have other layers in addition to the polyester layer and the mixed resin layer. Examples of the other layers include an adhesive layer containing an adhesive resin interposed between the polyester layer and the mixed resin layer. However, from the viewpoint of improving moldability and separability during recycling, it is preferable that the container does not include an adhesive layer.

[0051] The thickness of the mixed resin layer of the multilayer container of the present invention is preferably 1% or more of the total thickness, more preferably 1.5% or more, and even more preferably 2% or more. It is preferably 15% or less, more preferably 12.5% ​​or less, and even more preferably 10% or less. If the thickness of the mixed resin layer is within the above range, sufficient oxygen barrier properties are obtained and it is economical.

[0052] The mixed resin layer does not have to be laminated on the bottom or neck of the multi-layer container, and it is preferable that the mixed resin layer is present at the above-mentioned thickness and position over at least a part of the body, preferably the central part of the body, and more preferably 50% or more of the length of the body. From the viewpoint of balancing delamination resistance and oxygen barrier properties, the mixed resin layer preferably extends from the bottom of a support ring of the preform described below to a position about 20 to 40 mm from the center of the injection gate of the preform.

[0053] The total thickness of the multilayer container is preferably 50 μm to 500 μm, more preferably 100 μm to 450 μm, and even more preferably 200 μm to 400 μm. The total thickness here refers to the average value of the total thickness of all layers (resin layers) in the body of the multilayer container. From the viewpoints of oxygen barrier property, thermal stability, delamination resistance, and production, the capacity of the multilayer container is preferably 30 to 3,000 mL, more preferably 50 to 2,000 mL, even more preferably 100 to 1,500 mL, even more preferably 200 to 1,000 mL, and even more preferably 200 to 600 mL.

[0054] The multilayer container of the present invention is more preferably a liquid packaging container that is used by filling the interior of the hollow container with a liquid, and even more preferably a beverage packaging container. Examples of the liquid to be filled inside include beverages such as water, carbonated water, oxygenated water, hydrogenated water, milk, dairy products, juice, coffee, coffee drinks, carbonated soft drinks, tea, and alcoholic drinks; liquid seasonings such as sauces, soy sauce, syrups, mirin, and dressings; chemical products such as pesticides and insecticides; medicines; and detergents. In particular, beverages and carbonated beverages that are prone to deterioration in the presence of oxygen, such as beer, wine, coffee, coffee drinks, fruit juices, carbonated soft drinks, carbonated water, and tea, are preferred.

[0055] Furthermore, the multilayer container of the present invention has excellent oxygen barrier properties, and the oxygen permeability (cc / (day·bottle·0.21 atm)) of the container measured by the method described below is preferably 0.010 or less, more preferably 0.005 or less, and even more preferably 0.001 or less. The measurement method is to fill a 500 mL bottle with 100 mL of water, and circulate 1 atm nitrogen through the bottle at 20 mL / min under conditions of oxygen partial pressure of 0.21 atm, bottle internal humidity of 100% RH (relative humidity), external humidity of 50% RH, and temperature of 23° C., and after 200 hours, the amount of oxygen contained in the nitrogen that has circulated through the bottle is detected with a coulometric sensor, thereby obtaining the oxygen permeability. More specifically, the oxygen permeability of the container can be measured by the method described in the Examples.

[0056] [Manufacturing method of multi-layer containers] The multilayer container of the present invention can be produced by an appropriate method, which is selected in consideration of the structure of the molded product, etc. Specifically, the multilayer container can be produced by injecting a molten resin or resin composition from an injection molding machine into a mold to produce a preform, which is then blow-stretched (injection blow molding, injection stretch blow molding). Alternatively, the plastic can be obtained by extruding a molten resin or resin composition from an extrusion molding machine into a mold to obtain a parison, which is then blown in the mold (direct blow molding). The multi-layer container of the present invention is preferably produced by injection blow molding.

[0057] The multi-layer container of the present invention is preferably produced by biaxially stretching and blow molding a preform. The multilayer container of the present invention may be formed by cold parison molding or hot parison molding. Cold parison (two-stage molding) molding is a molding method in which the preform after injection molding is cooled to room temperature, stored, and then reheated in another device and supplied to blow molding. On the other hand, hot parison molding (one-stage molding) is a blow molding method in which the parison is not completely cooled to room temperature, but is preheated at the time of injection molding and temperature controlled before blowing, thereby performing blow molding. In hot parison molding, in many cases, an injection molding machine, a temperature control zone, and a blow molding machine are provided in the same molding machine unit, and preform injection molding and blow molding are performed.

[0058] A first embodiment of the method for producing a multilayer container of the present invention is an embodiment in which molding is performed by cold parison molding. Hereinafter, a description will be given with reference to Fig. 1. Fig. 1 is a conceptual schematic diagram showing each step of cold parison molding. However, it goes without saying that the first embodiment is not limited to the configuration shown in Fig. 1. In FIG. 1, first, a preform 1 is heated (FIG. 1(1)). The heating is performed by an infrared heater 2 or the like. Next, the heated preform 1 is subjected to biaxial stretch blow molding. That is, it is placed in a mold 3 (FIG. 1(2)) and is blow molded while being stretched by a stretch rod 4 (FIG. 1(3) and (4)). For example, the preform surface is heated and then stretched in the axial direction by mechanical means such as pressing with a core rod insert, and then high-pressure air, usually at 2 to 4 MPa, is blown to stretch it laterally, thereby forming a blow molded product. In order to improve the heat resistance of the container, a blow molding method that increases the crystallinity or reduces residual distortion may be combined. For example, there is a method (single blow molding) in which the surface of a multilayer preform is heated and then blow molded in a mold at a temperature above the glass transition point. Furthermore, it may be so-called double blow molding, which comprises a primary blow molding step in which the preform is biaxially stretched and blow molded to a size larger than the final shape, a step in which this primary blow molded product is heated and thermally shrunk to form a secondary intermediate molded product, and finally a secondary blow molding step in which this secondary intermediate molded product is blow molded into the final container shape. After the blow molding, the mold 3 is removed, and a multi-layer container 5 is obtained (FIG. 1 (5)).

[0059] In cold parison molding, the parison temperature before blow molding is determined in consideration of the glass transition temperature (Tg) of the resin constituting the multilayer container of the present invention. Before blow molding means, for example, the time immediately before blowing after passing through a preheating zone. The parison temperature is the glass transition temperature (Tg max ), and temperatures exceeding (Tg max +0.1)℃~(Tg max +50)°C temperature range is more preferred. In addition, the glass transition temperature (Tg min ) and the Tg max The difference is preferably not more than 40° C., and more preferably not more than 30° C. By setting the difference in this range, the blow moldability tends to be further improved. Furthermore, when at least one of the resins constituting the multilayer container of the present invention is a crystalline resin, the lowest crystallization temperature (Tc) of the crystalline resin is min ) and the glass transition temperature (Tg max ) is preferably larger. Specifically, Tc min -Tg maxIt is preferable that the temperature is 5°C or higher, and more preferably 10°C or higher. Tc min -Tg max The upper limit of the temperature is practically not more than 100° C. By setting the temperature in this range, the blow moldability tends to be further improved.

[0060] In addition, it is preferable to prepare a mixed resin in advance by mixing the polyamide resin (B), polyglycolic acid (C) and oxidation promoter (D) used in the mixed resin layer before molding the preform. The mixing may be dry blending or melt blending (melt kneading). That is, the components may be dry blended to prepare a mixed resin, or the components may be melt blended to prepare a mixed resin. Among these, dry blending is preferable from the viewpoint of reducing thermal history. Here, dry blending means mechanically mixing in the form of powder or pellets. For mixing, it is preferable to use a mixing device such as a tumbler mixer, ribbon mixer, Henschel mixer, or Banbury mixer. Alternatively, when subjecting to molding processing, a predetermined amount of polyglycolic acid (C) may be supplied by a feeder other than the feeder for supplying the polyamide resin (B), so that the mixed resin is prepared just before molding the parison. In addition, when the polyamide resin (B), the polyglycolic acid (C) and the oxidation promoter (D) are melt-kneaded, the temperature in the melt-kneading is not particularly limited, but from the viewpoint of the resin being sufficiently melted and sufficiently kneaded, it is preferably 300 to 255°C, more preferably 290 to 260°C, and even more preferably 285 to 265°C. In addition, the time for melt-kneading is not particularly limited, but from the viewpoint of the resin being uniformly mixed, it is preferably 10 to 600 seconds, more preferably 20 to 400 seconds, and even more preferably 30 to 300 seconds. The device used for melt-kneading is not particularly limited, but examples thereof include an open-type mixing roll, a non-open-type Banbury mixer, a kneader, a continuous kneader (such as a single-shaft kneader, a twin-shaft kneader, or a multi-shaft kneader), and the like. In addition, when other resins or other components are mixed into the polyester layer or the mixed resin layer, it is preferable to mix the polyamide resin (B), polyglycolic acid (C) and oxidation promoter (D) under the same conditions.

[0061] Next, the resin constituting the polyester layer is extruded from a first extruder, and the resin constituting the mixed resin layer is extruded from a second extruder to form a parison (multilayer preform). More specifically, it is preferable that the multilayer preform is formed by extrusion molding, co-injection molding, compression molding, or the like. In the extrusion molding, the resin constituting the polyester layer and the resin constituting the mixed resin layer are co-extruded to form a multi-layer preform. In the co-injection molding, the resin constituting the polyester layer and the resin constituting the mixed resin layer are each extruded into a mold and co-injected to form a multi-layer preform. In compression molding, for example, the resin constituting the mixed resin layer in a heated and molten state is intermittently extruded into an extrusion flow path in which the resin constituting the polyester layer in a heated and molten state flows, and the resin constituting the polyester layer surrounding substantially the entire extruded resin constituting the mixed resin layer is extruded from the extrusion port of the extrusion flow path, supplied to an appropriate molding die as a molten resin molding material, and then compression molded to form a multilayer preform. Among these, coinjection molding is preferred from the viewpoint of productivity. EXAMPLES

[0062] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to these examples.

[0063] The resins used in the examples and comparative examples are as follows. <Polyester resin (A)> PET: Polyethylene terephthalate (intrinsic viscosity: 0.83 dL / g), product name: BK2180, manufactured by Mitsubishi Chemical Corporation (melting point 248°C) <Polyamide resin (B)> MXD6: Poly(metaxylylene adipamide) (relative viscosity: 2.7, melting point = 240 ± 5°C), product name: MX nylon S6007, manufactured by Mitsubishi Gas Chemical Company, Inc. <Polyglycolic acid (C)> PGA (Polyglycolic Acid) (glass transition temperature: 38°C, melting point: 221°C, crystallization temperature: 91°C) <Prooxidant (D)> Cobalt stearate: Cobalt(II) stearate, manufactured by Wako Pure Chemical Industries, Ltd.

[0064] [Measurement and evaluation method] <Oxygen permeability of container (oxygen barrier property of container)> An oxygen permeability measuring device (manufactured by MOCON, product name "OX-TRAN 2 / 61") was used. A 500 mL bottle prepared in each of the Examples and Comparative Examples was filled with 100 mL of water, and nitrogen at 1 atm was passed through the bottle at 20 mL / min under conditions of an oxygen partial pressure of 0.21 atm, an internal bottle humidity of 100% RH (relative humidity), an external humidity of 50% RH, and a temperature of 23°C. After 200 hours, the amount of oxygen contained in the nitrogen that had passed through the bottle was detected with a coulometric sensor to measure the oxygen permeability (cc / (day bottle 0.21 atm)). The smaller the oxygen permeability, the better the oxygen barrier property.

[0065] <Dimensional change rate (thermal stability)> Two marks were made on the side of the 500 mL bottle obtained in each Example and Comparative Example, and the bottle was filled with 500 g of water at 60° C. and stored for 24 hours in a room with an ambient temperature of 60° C. The distance (dimension) between the two marks was measured before and after storage, and the rate of change ([dimension before storage - dimension after storage] / dimension before storage (%)) was taken as the rate of dimensional change. The smaller the rate of dimensional change, the more excellent the thermal stability.

[0066] <Side impact test (delamination resistance)> The resulting multi-layer bottle was filled with 500 mL of carbonated water and stored for one week in an environment of 23°C and 50% RH. Using a side impact tester (a device with a 3 kg weight attached to the end of a pendulum that is lowered at a 90° angle to the bottle to apply impact force to the bottle body), impacts were repeatedly applied to the body of the bottle containing the carbonated water after one week of storage. Delamination resistance was evaluated based on the number of tests required until the polyester layer and polyamide layer peeled off. If the polyester layer and polyamide layer had not peeled off after 40 tests, the evaluation was "40 or more times." The more tests required until the polyester layer and polyamide layer peeled off, the better the delamination resistance.

[0067] Example 1 <Preform manufacturing> For the mixed resin layer, MXD6 (polyamide resin (B)), PGA (polyglycolic acid (C)), and cobalt stearate were placed in a tumbler and dry blended to obtain the ratio shown in the middle layer of Table 1. PET (polyester resin (A)) was used for the polyester layer. The materials for each layer were placed in the hopper of an injection blow molding machine, and a multi-layer hot runner mold was used to inject the materials under the conditions shown below to fill the cavity, thereby obtaining a preform (25 g) with a three-layer structure of polyester layer / mixed resin layer / polyester layer. The thickness of each layer was adjusted to 8:1:8. The shape of the preform was 92 mm in total length, 22 mm in outer diameter, and 3.9 mm in thickness. Skin side injection cylinder temperature: 285℃ Core side injection cylinder temperature: 265℃ Resin flow path temperature in mold: 290℃ Mold cooling water temperature: 15℃

[0068] <Manufacturing of multi-layer bottles> The preform produced by the above-mentioned manufacturing method was used to mold a bottle. Specifically, the obtained preform was biaxially stretched and blow molded using a biaxially stretched blow molding machine (manufactured by Frontier Corporation, model EFB1000ET) to obtain a petaloid-shaped bottle. The total length of the bottle was 223 mm, the outer diameter was 65 mm, and the internal volume was 500 mL (surface area: 0.04 m). 2 The thickness of the bottle was 0.35 mm (average body thickness: 0.35 mm) and the bottom was petaloid shaped. No dimples were provided on the body. The biaxial stretch blow molding conditions were as shown below. The neck and bottom of the obtained multi-layer bottle were formed only from the polyester layer. The multi-layer bottle thus obtained was subjected to the above-mentioned measurements and evaluations. The results are shown in Table 1. Preform heating temperature: 110℃ Primary blow pressure: 0.9MPa Secondary blow pressure: 2.5MPa Primary blow delay time: 0.30 sec First blow time: 0.30 sec Secondary blow time: 2.0 sec Blow exhaust time: 0.6 sec Mold temperature: 30℃

[0069] Examples 2 and 3 and Comparative Example 2 Bottles were molded in the same manner as in Example 1, except that the ratios of MXD6 (polyamide resin (B)) and PGA (polyglycolic acid (C)) for the mixed resin layer were changed to those shown in Table 1. The above-mentioned measurements and evaluations were carried out on the obtained multi-layer bottle. The results are shown in Table 1.

[0070] Example 4 A bottle was molded in the same manner as in Example 1, except that the PET (polyester resin (A)) for the polyester layers used in the inner and outer layers was changed to a dry blend of the PET for the polyester layers and a colorant (product name HOLCOMER UHT: manufactured by Holland Colours, a masterbatch of a polyester resin containing a pigment) in a mass ratio of (PET / colorant) 90 / 10. The above-mentioned measurements and evaluations were carried out on the obtained multi-layer bottle. The results are shown in Table 1.

[0071] Example 5 Bottles were molded in the same manner as in Example 1, except that the PET (polyester resin (A)) for the polyester layers used in the inner and outer layers was changed to a dry blend of the PET for the polyester layers and PGA (polyglycolic acid (C)) in the ratio shown in Table 1. The above-mentioned measurements and evaluations were carried out on the obtained multi-layer bottle. The results are shown in Table 1.

[0072] Comparative Example 1 A bottle was molded in the same manner as in Example 1, except that cobalt stearate was not used in the mixed resin layer. The obtained multi-layer bottle was subjected to the above-mentioned measurements and evaluations. The results are shown in Table 1.

[0073] Comparative Example 3 A bottle was molded in the same manner as in Example 1, except that PET (polyester resin (A)) was dry-blended in the ratio shown in Table 1, instead of PGA (polyglycolic acid (C)) for the mixed resin layer. The above-mentioned measurements and evaluations were carried out on the obtained multi-layer bottle. The results are shown in Table 1.

[0074] Comparative Example 4 A bottle was molded in the same manner as in Example 1, except that MXD6 (polyamide resin (B)) for the mixed resin layer was not used and PGA (polyglycolic acid (C)) was changed to the ratio shown in Table 1. The above-mentioned measurements and evaluations were carried out on the obtained multi-layer bottle. The results are shown in Table 1.

[0075] [Table 1] As shown in Table 1, in all of Examples 1 to 5 which met the requirements of the present invention, multilayer containers having high oxygen barrier properties, high thermal dimensional stability, and excellent delamination resistance were obtained. [Industrial Applicability]

[0076] According to the present invention, a multi-layer container having excellent oxygen barrier properties, thermal stability, and delamination resistance can be obtained, and therefore the container can be suitably used as a container for storing foods and beverages, such as oils, seasonings, carbonated drinks, alcoholic beverages, coffee, fruit juices, teas, etc., whose contents are susceptible to oxidation by oxygen, reach high temperatures during filling or storage, and are often subjected to impacts. [Explanation of symbols]

[0077] 1 Preform 2 Infrared heater 3. Mold 4 Extension rod 5 Multilayer container

Claims

1. A polyester layer containing an aromatic polyester resin (A); a mixed resin layer containing a polyamide resin (B), a polyglycolic acid (C) and an oxidation promoter (D); a mass ratio [(B) / (C)] of the polyamide resin (B) to the polyglycolic acid (C) in the mixed resin layer is 55 / 45 to 70 / 30; The polyamide resin (B) has a diamine-derived structural unit containing 70 mol % or more of a xylylenediamine-derived structural unit and a dicarboxylic acid-derived structural unit containing 70 mol % or more of a C4-20 α,ω-linear aliphatic dicarboxylic acid-derived structural unit, A multi-layer container in which the pro-oxidant (D) is an aliphatic carboxylate of cobalt.

2. The multilayer container according to claim 1, which has a 2 to 5 layer structure.

3. 3. The multilayer container according to claim 1 or 2, which has a two-layer structure in which a polyester layer / mixed resin layer are laminated in this order from the outside of the container, a three-layer structure in which a polyester layer / mixed resin layer / polyester layer are laminated in this order, or a five-layer structure in which a polyester layer / mixed resin layer / polyester layer / mixed resin layer / polyester layer are laminated in this order.

4. 4. The multilayer container according to claim 1, wherein the oxidation promoter (D) is at least one member selected from the group consisting of cobalt octanoate, cobalt naphthenate, cobalt acetate, and cobalt stearate.

5. The multilayer container according to any one of claims 1 to 4, wherein the thickness of all layers of the multilayer container is 50 to 500 µm.

6. The multilayer container according to any one of claims 1 to 5, having a capacity of 200 to 600 mL.

7. The multilayer container according to any one of claims 1 to 6, wherein the aromatic polyester resin (A) has a structural unit derived from a dicarboxylic acid containing 90 mol % or more of a structural unit derived from terephthalic acid, and a structural unit derived from a diol containing 90 mol % or more of a structural unit derived from ethylene glycol.

8. The multilayer container according to any one of claims 1 to 7, wherein the polyamide resin (B) has a diamine-derived structural unit containing 80 mol% or more of a xylylenediamine-derived structural unit and a dicarboxylic acid-derived structural unit containing 80 mol% or more of adipic acid-derived structural unit.

9. 9. The multilayer container according to claim 1, wherein the polyester layer comprises an aromatic polyester resin (A) and a polyglycolic acid (C).

Citation Information

Patent Citations

  • Plastic multilayer structure

    JP2003300292A

  • Plastic container

    JP2005271959A

  • Synthetic resin-made container

    JP2006117269A

  • Resin composition and multilayer structure

    JP2007211159A

  • Aromatic polyester resin-based stretched article

    JP2008231316A